Microscopical and phylogenetic analysis of Theileria annulata in Iraqi local breed cattle - Hadeel Hadi Albayati; Alaa Mohammed Al Khafaji; Amal kamel; Hassan Al-karagoly (Veterinary Integrative Sciences, 2023)
The development of cattle industry in Iraq and its neighboring countries may be hampered by Theileria annulata (T. annulata) infection. In the present work, the cytochrome b gene (cyt-b) sequences were used to infer the phylogenetic relationships of T. annulata. Fifty blood samples collected randomly from 10 farms of Iraqi local breed cattle in Al-Diwaniyah province were analyzed for piroplasm using microscopic and molecular techniques. Microscopic examination revealed that 37 (74%) of the 50 blood samples examined were infected. In addition, the PCR test showed that 23 (62.2%) of the 37 blood samples (which tested positive (microscopically) were positive. The analysis of the cyt-b 1092 bp gene of T. annulata reported the presence of six genetically related clones. These six clones have been deposited in GenBank as [ON706262, ON706263, ON706264, ON706265, ON706266, and ON706267], and when compared to the T. annulata cyt-b gene (XM949625) from the GenBank database, a unique polymorphism at sixteen sites was discovered. Furthermore, the alignment of our amino acid sequences with the reference sequence reveals thirteen non-synonymous mutations in codons 11, 22, 33, 63, 103, 128, 130, 129, 172,178, and 190, and three silent mutations in codons 124, 128, and 275. Moreover, phylogenetically, our study clones were related to Iraqi, Indian, and Turkish clones. In conclusion, depending on the phylogenetic analysis the current study identified six T. annulata parasite isolates in Iraqi local breed cattle that were genetically related to the Indian, Iraqi, and Turkish clones.